Robust Video Watermarking Scheme Based on Intra-Coding Process in MPEG-2 Style - Rakesh Ahuja; S. S. Bedi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The proposed scheme implemented a semi blind digital watermarking method for video exploiting MPEG-2 standard. The watermark is inserted into selected high frequency coefficients of plain types of discrete cosine transform blocks instead of edge and texture blocks during intra coding process. The selection is essential because the error in such type of blocks is less sensitive to human eyes as compared to other categories of blocks. Therefore, the perceptibility of watermarked video does not degraded sharply. Visual quality is also maintained as motion vectors used for generating the motion compensated images are untouched during the entire watermarking process. Experimental results revealed that the scheme is not only robust to re-compression attack, spatial synchronization attacks like cropping, rotation but also strong to temporal synchronization attacks like frame inserting, deleting, swapping and averaging. The superiority of the anticipated method is obtaining the best sturdiness results contrast to the recently delivered schemes.